(untitled) (Comprehensive Journal of Science, 2025)
The main objective of this study was to identify the role of using artificial intelligence (AI) techniques in improving the quality of accounting information by enhancing the effectiveness and efficiency of internal control systems in Libyan commercial banks. This was achieved by surveying a sample of employees working in the financial management and information technology departments of Libyan commercial banks. To achieve this goal, the study adopted both the inductive and deductive approaches, and a questionnaire was used as the main tool for data collection, distributed to the study participants. The responses were statistically analyzed using the SPSS statistical package. The study concluded that there is a significant role for the use of artificial intelligence techniques in improving the quality of accounting information through enhancing the effectiveness and efficiency of internal control systems in commercial banks. Moreover, a partial mediation effect was found, as the internal control system, acting as a mediating variable, transmits part of the impact of using artificial intelligence techniques (independent variable) on improving the quality of accounting information.